Design and Characterization of Fluconazole Loaded Nanosponges Containing Topical Gel Preparation: Pharmaceutical Science-Pharmaceutics - R. Jadhav, Khanderao; Y. Pawar, Ashish; S. Sanap, Ashwini; P. Rathod, Sharayu; S. Malpure, Prashant; S. Bachhav, Rishikesh (International Journal of Life Science and Pharma Research, 2022)
The main aim and objective of this research was to develop and evaluate Fluconazole loaded nanosponges and formulate them as suitable topical gels for delivering the drug systemically after topical application. Fluconazole (FLZ) is a potent triazole anti fungistatic drug; topical administration of novel Fluconazole resulted in systemic absorption, for improved therapeutic effect and better dispersibility as compared to conventional topical formulation. Fluconazole (FLZ) nanosponges prepared by using emulsion solvent diffusion method to improve topical permeation. Nanosponges were formulated successfully using ethyl cellulose and Eudragit RS 100 as polymer, polyvinyl alcohol as the surfactant, and dichloromethane as solvent. The optimised batch of fluconazole loaded nanosponges used to prepare topical gel using different concentrations of carbopol gel. The prepared nanosponges were evaluated by various tests like production yield, drug entrapment efficiency, FTIR, particle size, zeta potential, SEM study. The entrapment efficiency and production yield were excellent. Based on the entrapment efficiency and production yield,out of ten formulations batches of nanosponges was evaluated and from that batch F3 was optimised.Optimized batch F3 containing FLZ and EC in the ratio of 1:3 showed optimum physicochemical and release characteristics. The optimised batch F3 of ethyl cellulose shows highest entrapment efficiency as 97.97% and production yield as 93.85% resp. A complex Fourier transform infrared (FTIR) study examines the formation in the nanosponge structure. The nanosponges had particle size in the range of 234.95 to 374.26 nm. The Zeta Potential was strong enough to produce stable formulations. The zeta potential of optimised batch nanosponges was found to be - 25.05. SEM analysis of optimized batch F3 confirms that nanosponges were spherical in size with a porous and smooth surface. The formulated fluconazole topical gel were characterized for pH, actual drug content, viscosity, spreadability, In -Vitro drug release study. The in -vitro drug release showed maximum drug release of topical gel i.e. 88.34% in 8 hours. The present study demonstrates that, an antifungal drug Fluconazole is formulated in the form of nanosponges topical gel for the antifungal activity and can be best suitable approach in novel drug delivery system than conventional gel. Hence it is concluded that above topical gel formulation of fluconazole loaded nanosponges can be used in treatment of fungal infection.